2021
DOI: 10.1002/mnfr.202100602
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Pork Induces Hepatic Steatosis by Impairing Thyroid Hormone Function in Mice

Abstract: Scope: Recent studies have linked high consumption of red and processed meats to an increased risk of non-alcoholic fatty liver disease, and cooking-induced oxidation of proteins and amino acids might be contributing factors. Herein, this study investigates the influence of oxidized pork and the protein oxidation biomarker dityrosine (Dityr) on hepatic steatosis in mice. Methods and Results: Low-and high-oxidative injury pork (LOP and HOP) are freeze-dried to prepare mouse diets. Mice are fed a diet of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Previous studies found that changes in the inflammatory profile and oxidation status (REDOX) induce increased D3 activity in acute illness situations [36][37][38]. Here we observed that in a model of chronic disease, the accumulation of hepatic fat, via high-fat diet, induces inflammatory changes and a consequent increase in the production of reactive oxygen species (ROS) [39][40][41][42][43][44]. These data reinforce the direct association between the inflammatory profile and the REDOX state with diminished T3 levels, via an increase in D3 activity and a reduction in D1.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies found that changes in the inflammatory profile and oxidation status (REDOX) induce increased D3 activity in acute illness situations [36][37][38]. Here we observed that in a model of chronic disease, the accumulation of hepatic fat, via high-fat diet, induces inflammatory changes and a consequent increase in the production of reactive oxygen species (ROS) [39][40][41][42][43][44]. These data reinforce the direct association between the inflammatory profile and the REDOX state with diminished T3 levels, via an increase in D3 activity and a reduction in D1.…”
Section: Discussionmentioning
confidence: 74%
“…The cell studies used the administration of FFAs [ 29 ] or palmitic and oleic acid [ 30 ]. The animal models show heterogeneity regarding the induction of the model, but the vast majority used ae high fat diet (HFD) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]; one study used a pork-derived diet [ 41 ], while other models did not induce MAFLD but induced situations of hypo and hyperthyroidism [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], subsequently evaluating its effects on the liver. Most of the selected articles included some type of hormone supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term consumption of dityrosine-rich food is associated with a variety of diseases, such as liver and kidney fibrosis, obesity, diabetes, cardiovascular disease, Alzheimer's disease, and aging (B. Ding, Tang et al, 2017;Ge et al, 2021Ge et al, , 2022Gutiérrez et al, 2015; Z. L. Li et al, 2017;Z. L. Li et al, 2016;Lu et al, 2020;Mo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…At that time, dityrosine research was mainly focused on food and biological samples. Recent research indicates that dityrosine can act as an oxidative-stress marker in the human body, inducing oxidative stress and metabolic syndrome (Ge et al, 2022;Lu et al, 2020;Yang, Zhang et al, 2017). This discovery has revived dityrosine research, with emphasis on its biochemistry and pathobiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation